Distributions of Energy Losses by Fast Ions along Their Propagation Paths in Solids - Ilyina, V.V.; Makarets, M.V. (Відділення фізики і астрономії НАН України, 2010)
The integro-differential equations for cumulants of the distribution function that describes energy losses by fast ions during their propagation in solids have been obtained. The equations differ from those obtained by other authors by one new term. The term describes accurately the process of slowing down of an ion at the start of its path. The equations have been numerically solved for the first seven cumulants of the distribution function for both elastic and inelastic energy losses, and the results have been compared with the results for ion ranges. It has been found that: 1) for energies in the interval 1 keV-1 GeV, the average ranges with energy losses are approximately 30-90% of the ion ranges; 2) for low energies, the straggling of the distribution of energy losses are slightly larger than or equal to the straggling of the distribution of ion ranges, while, for high energies, the former can be 10 times as large as the latter; 3) for low energies, the skewnesses and excesses of the distributions of energy losses and ion ranges are approximately the same, while their changes for the former at higher energies are several orders smaller than those for the latter. This implies that the distribution of energy losses are wider and closer to the normal distribution than the distribution of ion ranges. We show that these properties of energy loss distributions are a result of the inclusion of the new terms in the equations which dominate at high energies. Отримано iнтегродиференцiальнi рiвняння для кумулянтiв функцiї розподiлу втрат енергiї швидких iонiв вздовж їх шляху у твердому тiлi, у яких враховано втрати енергiї починаючи iз точки старту. Рiвняння для перших семи кумулянтiв розподiлiв втрат енергiї у пружних, непружних та обох типах зiткнень розв’язанi чисельно за допомогою методу, розвинутого авторами ранiше, на iнтервалi енергiй iонiв 1 кеВ–1 ГеВ. Їх порiвняння з параметрами розподiлу пробiгiв iонiв показало, що: 1) середнiй шлях за розподiлом втрат енергiї становить 30–90% повного пробiгу iонiв; 2) при низьких енергiях страгглiнг за розподiлом втрат енергiї дещо бiльший або однаковий iз страгглiнгом за розподiлом пробiгiв iонiв, а при високих енергiях перший перевищує останнiй у десятки разiв; 3) скiсностi i ексцеси розподiлiв при низьких енергiях вiдповiдно близькi, у той час як при високих енергiях їх змiна для розподiлу втрат енергiї на кiлька порядкiв менша, нiж для розподiлу пробiгiв iонiв. Звiдси випливає, що розподiл втрат енергiї ширший i значно ближчий до нормального, нiж розподiл пробiгiв iонiв при всiх енергiях iмплантацiї. Показано, що цi властивостi розподiлу втрат енергiї зумовленi новими членами у рiвняннях, якi не враховувалися ранiше, але домiнують при високих енергiях. Получены интегродифференциальные уравнения для кумулянтов функции распределения потерь энергии быстрых ионов вдоль их пути в твердом теле, в которых учтены потери энергии начиная с точки старта. Уравнения для первых семи кумулянтов распределений потерь энергии в упругих, неупругих и обеих типах столкновений решены численно с помощью метода, развитого авторами ранее, на интервале энергий ионов 1 кэВ–1 ГэВ. Их сравнение с параметрами распределения пробегов ионов показало, что: 1) средний путь с потерей энергии составляет 30–90% полного пробега иона; 2) при низких энергиях страгглинг распределения потерь энергии немного больше или одинаков со страгглингом распределения пробегов ионов, а при высоких энергиях первый превышает последний в десятки раз; 3) скошенности и эксцессы распределений при низких энергиях соответственно близки, в то время как при высоких энергиях их изменение для распределения потерь энергии на несколько порядков меньше, чем для распределения пробегов ионов. Отсюда следует, что распределение потерь энергии более широкое и ближе к нормальному, чем распределение пробегов ионов для всех энергий имплантации. Показано, что эти свойства распределения потерь энергии обусловлены новыми членами в уравнениях, которые не учитывались ранее, но доминируют при высоких энергиях.